2009
DOI: 10.1111/j.1600-0625.2009.00874.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of 12‐LOX and COX‐2 reduces the proliferation of human epidermoid carcinoma cells (A431) by modulating the ERK and PI3K‐Akt signalling pathways

Abstract: Eicosanoids, the oxygenated metabolites of arachidonic acid (AA), mediate a variety of human diseases, such as cancer, inflammation and arthritis. To evaluate the role of eicosanoids in epidermoid carcinoma, the expression of AA metabolizing enzymes, such as lipoxygenases (LOXs) and cyclooxygenases (COXs), was analysed in a human epidermoid carcinoma cell line (A431). These studies revealed overexpression of 12-R-LOX and COX-2 in A431 cells. Baicalein (a 12-LOX inhibitor) and celecoxib (a COX-2 inhibitor) sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 30 publications
1
36
0
Order By: Relevance
“…Although several studies have reported that COX2 activation linked to activation of Akt and ERK is involved in cell growth or inflammation [38,39,49,50,63], little is known that the role of COX-2 activation associated with Akt/ERK pathway in an ability of 5-HT uptake. Celecoxib has no effect on the TNFα-induced activation of Akt and ERK to regulate inflammation in murine fibroblast cell line NIH-3T3 [63].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although several studies have reported that COX2 activation linked to activation of Akt and ERK is involved in cell growth or inflammation [38,39,49,50,63], little is known that the role of COX-2 activation associated with Akt/ERK pathway in an ability of 5-HT uptake. Celecoxib has no effect on the TNFα-induced activation of Akt and ERK to regulate inflammation in murine fibroblast cell line NIH-3T3 [63].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that COX-2 inhibitor also lowers Akt activation, which mediates cell growth or inflammation [38,49,50]. However, little is known that the role of COX-2 induction linked to activation of Akt in an ability of 5-HT uptake.…”
Section: Inhibiting Pi3k/akt Activation Blocked Ifn-α-induced Erk Actmentioning
confidence: 97%
“…Arachidonate 12R-lipoxygenase (Alox12b) shown to be involved in mouse epidermal differentiation and skin barrier formation is induced in epidermoid carcinomas contributing to the tumor cell proliferation [18]. Genetic inactivation of Alox12b leads to thickening of the epidermis, hyper-proliferation of epidermal cells, and severe hyperkeratosis in mice [19], while the ALOX12B inhibition enhances human tumor cell death [20].…”
Section: Introductionmentioning
confidence: 99%
“…However, little is known about the molecular mechanism of the COX-2 pathway in the regulation of HNSCC cell growth. Molecular mechanism of cell apoptosis by COX-2/PGE 2 through phosphatidylinositol 3-kinase (PI3K)/AKT pathway has been suggested in human epidermoid carcinoma cells (Agarwal et al, 2009).…”
Section: Cox and Hncmentioning
confidence: 99%
“…LOX metabolites may enhance cancer cell survival through an increase in Bcl-2. In addition, they can upregulate the p-ERK and p-AKT levels, suggesting the involvement of ERK and AKT pathways in the LOX-mediated regulation of growth in cancer cells (Agarwal et al, 2009). However, it was found that metabolism of AA by 5-LOX activity promotes survival of cancer cells via signaling through PKCε, a pro-survival serine/threonine kinase which is not dependent on the AKT and ERK-pathway (Sarveswaran et al, 2011).…”
Section: Molecular Mechanisms Of Lox-mediated Hnc Developmentmentioning
confidence: 99%